Should the Postgraduate Dental Curriculum Be Revamped? - A Stress Assessment Study - B R Premalatha; Usha Hegde; Priyanka Nitin; H S Sreeshyla; Nitin V Muralidhar; P Swetha (Journal of Multidisciplinary Dental Research)
Dental education is widely regarded as a demanding experience. Information about the stress sources and their degree is crucial since it will aid in the development of appropriate interventional methods for the student's overall development. Thus, our study was aimed at assessing the different forms of stress that affect Postgraduate dentistry students, as well as their attitudes toward psychiatric therapies. The study was conducted on 93 postgraduate dental students at a dental institution in Mysuru, India, using a cross-sectional questionnaire-based survey format. The information gathered was statistically examined. The mean and standard deviation were used in the quantitative analysis. The mean of all stressor scores was compared between groups using an independent sample t-test and one-way ANOVA. The Chi-square test was employed to examine qualitative data. The overall stress level among postgraduate dental students was high. All the year students demonstrated a similar trend with a high level of academic stress followed by health-related and psychosocial stress. The academic stress increased as the year of study progressed. We discovered no differences in stress perception between male and female students. In addition, a notable proportion of the participants had a favourable attitude toward psychiatric therapy. Stress levels among postgraduate dental students were found to be high in our study. This indicates a need for upgrading the current postgraduate dental educational system to be less stressful. Keywords: Dental education, Dental students, Mental health, Postgraduation, Stress, Stressors